Memperkuat Pajak Karbon: Menerapkan Perjanjian Paris dan Ekonomi Hijau di Indonesia - Ananta, Ahmad RIzal Roby; Abidin, Ahmad Dzaki; Jhoncilla, Iqbal Aryawidya (Hang Tuah Law Journal, 2025)
Climate change triggered by greenhouse gas emissions from fossil fuels is increasingly threatening the ecosystem and the global economy. A carbon tax is one of the policy instruments implemented in various countries, including Indonesia, to reduce emissions and encourage the transition to a green economy. Indonesia adopted this policy through Law No. 7 of 2021 on Carbon Taxes, with an initial rate of IDR 30 per kg CO₂e (USD 2 per ton CO₂e), making it one of the lowest in the world. This study aims to evaluate the effectiveness of the carbon tax policy in Indonesia by comparing it with Sweden. This country has implemented a carbon tax since 1991 and has succeeded in reducing emissions by 27%. This study uses a normative approach with comparative law, statutory, and conceptual approaches. Data were collected from primary regulations, scientific journals, and international reports related to carbon taxes. The results show that the implementation of the carbon tax in Indonesia still faces various obstacles, such as low rates, dependence on fossil fuels, and suboptimal carbon trading mechanisms.